Тhe astana process and its role in the resolution of the syrian conflict - Kublashev, B.A.; Nurgalieva, A. M. (Жәңгір хан атындағы БҚАТУ, 2023)
This article examines the role of the Astana process in the political and diplomatic settlement of the Syrian conflict, which is characterized by the involvement of not only the main states in the region but also international organizations, politico-military groupings, and world powers. В данной статье рассматривается роль Астанинского процесса в политико-дипломатическом урегулировании сирийского конфликта, которое характеризуется вовлечением в него не только основных государств региона, но и международных организаций, военно-политических группировок, мировых держав.
«ҒЫЛЫМҒА ЖОЛ – 2023» білім алушыларға арналған халықаралық ғылыми-тәжірибелік конференциясының МАТЕРИАЛДАР ЖИНАҒЫ
СБОРНИК МАТЕРИАЛОВ Международной научно-практической конференции обучающихся «ПУТЬ В НАУКУ – 2023»
66.4 K89 Kublashev BA.. Тhe astana process and its role in the resolution of the syrian conflict / A. Kublashev, A. M. Nurgalieva, науч. рук. - Текст : непосредственный // Ғылымға жол-2023: білім алушыларға арналған халықаралық ғылыми-тәжірибелік конф. мат. жинағы (12 сәуір 2023 ж.). = Путь в науку-2023: сб. мат. междунар. науч.-практ. конф. обучающихся (12 апреля 2023 г.). = THE PATH TO SCIENCE – 2023: collected papers of the International Scientific-Practical Conference of students (12th of April, 2023). - Орал: Жәңгір хан атындағы БҚАТУ. - 2023. - Т. ІІ. - Б. 512-517 (Орал)
Keywords: отечественное издание; ЗКАТУ; конференции; астанинский процесс; мировая политика; внешняя политика; миротворчество; аstana process; peacekeeping; global politics; урегулирование; сирийский конфликт